KOMPARASI FILSAFAT MATERIALISME ANTARA KARL MARX DAN CĀRVĀKA RAMKRISHNA BATTACHARYA - Pande Made Adhi Satria Wicaksana; I Ketut Wisarja; I Komang Suastika Arimbawa (Sanjiwani: Jurnal Filsafat, 2022)
Materialism is a philosophical understanding that is widespread and is known by many people in the world. Many world thinkers make materialism the main topic in their works. Karl Marx and Ramkrishna Battacharya are two figures of materialism who represent western philosophy and eastern philosophy, respectively. The purpose of this study is to compare and look at the similarities and differences in the materialism concepts of both Karl Marx and Cārvāka Ramkrishna Battacharya and see how relevant and implication the materialism concepts of Karl Marx and Cārvāka Ramkrishna Battacharya are. The method used in this study is a qualitative method with the analysis technique of the Miles and Huberman model where the data collection, data reduction, data display and verification processes are carried out where the data collection methods used are through documentation, library research, and online data searching. This study found a slight difference in the concept of materialism of Karl Marx with Cārvāka Ramkrishna Battacharya. The materialism concepts of Karl Marx and Cārvāka Ramkrishna Battacharya also have an influence through relevance which has implications for the lives of Indonesian people to this day. The concept of materialism from Karl Marx and Cārvāka Ramkrishna Battacharya ultimately has a significant impact, although there are differences in each of the concepts of materialism.